Education premium and the compound impact of universities on their regional economy - Janzen, Katrin; Panitz, Robert; Glückler, Johannes (Research policy, 2022)
Although the positive impact of higher education on regional economies is widely recognized, empirical assessment of the magnitude of its periodic financial impact remains a puzzle. Conventional impact studies have focused on the regional effects of periodic university spending, neglecting the core functions of higher education institutions. To overcome these shortcomings, we develop the concept of a differential regional education premium and implement it in an extended regional multiplier model. The new model integrates university expenditures and education into a compound effect on regional gross value added. Empirically, we find that the education premium increases the traditional effects of state universities in Baden-Württemberg by 68 percent. Generally, the model can be applied to other regions internationally by adapting to regional factors, such as graduate retention, tuition fees, wage levels and occupational qualifications in regional labor markets.
Available online 30 October 2021
Gesehen am 01.12.2021